Women in tech a practical guide to increasing gender diversity and inclusion - Dee, Hannah; Herman, Clem; Moore, Sharon; Palmer, Andrea; Shah, Shilpa (BCS, The Chartered Institute for IT, 2021)
This guide offers expertise, initiatives and true stories to support those wishing to bring greater gender diversity into the workplace. It aims to inform regarding background, theory and policy; advise on concrete actions that can be undertaken, and to be an exemplar for the tech industry in the form of real-world case studies.
Includes index
Keywords: Women in technology; Women in technology -- Case studies; Femmes en technologie; Femmes en technologie; Études de cas; Ethical & social aspects of computing; Office & workplace; Gender studies: women; Business & management; COMPUTERS / Social Aspects; SOCIAL SCIENCE / Gender Studies; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Women in Business; BUSINESS & ECONOMICS / General; Digital and information technologies: social and ethical aspects; Office and workplace; Gender studies: women and girls; Business and Management; Case studies